(untitled) (Global Journal of Medical Research, 2011)
Objective : This study aims to determine the prevalence and determinants of choice of contraceptive methods among rural women in Osun state, Nigeria. Materials and Methods : Descriptive cross-sectional, conducted among 612 women of reproductive age group, uutilising the multi-stage sampling technique. Results : Majority of the respondents, 538(87.8%) were within the age group 20 years and above and married (86.3%). More than half 406(66.3%) were currently using a modern contraceptive method, 41(6.7%) and 4(0.7%) were using natural and traditional methods respectively, however, 161(26.3%) were not using any method, main reasons being affordability and availability 184(41.2%), and reliability (20.1%). The most significant socio-demographic determinants of ever use of contraceptives were religion and family setting, p-value 0.001 and 0.001 respectively. Conclusion : The point prevalence rate of contraception among the rural women was 66.3%, with fear of side effect and husbands’ disapproval among other reasons being the main reasons for non use.